Geotextile encased columns (GEC) used as pressure-relief system. Instrumented bridge abutment case study on soft soil. Issue 3 (June 2017) - Schnaid, F.; Winter, D.; Silva, A.E.F.; Alexiew, D.; Küster, V.
Abstract: Geosynthetic Encased Sand Columns (GEC) have been frequently adopted in geo-engineering practice to improve bearing capacity, reduce settlements and accelerate consolidation in saturated soft cohesive ground (e.g. Alexiew et al, 2005; Alexiew et al., 2012; Raithel et al, 2005). The present paper extends these early views by introducing the use of columns to reduce the magnitude of horizontal earth pressures acting on structures adjacent to compaction fills. The monitoring program of a full-scale bridge abutment on soft soil supported by GECs and geogrid reinforced system is described, where field performance is monitored with pressure cells, electrical piezometers, inclinometers and settlement plates. Analytical and numerical analyses have been performed to help on interpreting experimental measurements. The collected database is interpreted to demonstrate that GEC can reduce by up to 50% the horizontal earth pressure over bridge border foundation piles when compared to values predicted for unreinforced ground and demonstrate that the work conformed to acceptable limits of behavior.